PEMBELAJARAN NATURE OF SCIENCE (NOS) BERBANTUAN LKS UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN MENUMBUHKAN LITERASI SAINS SISWA DI SMA NEGERI 1 PEMENANG - Ulfaturrohmi Ulfaturrohmi; Hunaepi Hunaepi; Puri Indah Lesmana (Bioscientist : Jurnal Ilmiah Biologi, 2014)
Based on observations made in SMAN 1 Pemenang of North Lombok Regency found that the classical completeness obtained far from the indicator that has been determined. The low learning outcomes of students are thought to occur because the presentation is more frequent using conventional methods and no practicum activities. The Nature of Science (NOS) Learning Model invites students to be able to train students 'skills in improving the skills of process skills so as to enhance their cognitive abilities and foster students' literacy skills. This type of research is classroom action research conducted in 2 cycles consisting of planning, implementation, observation, evaluation and reflection. The purpose of this study is to improve cognitive abilities and foster students' literacy skills. The instruments used in this research are test sheets and observation sheets. Research data in the form of students' cognitive abilities taken with the technique of test in the form of multiple choice and description obtained the results of learning completeness 61.53% in the first cycle and 85.00% in the second cycle. While the data of science literacy capability is taken with observation technique which is done in every cycle with observation technique obtained the average score of students science literacy ability of 72 in the first cycle and 85.93 in the second cycle which is included in the category is very high and is in the range of 81.25 - 100. Implementation of the Nature of Science (NOS) model can improve students' cognitive abilities and literacy skills.